Knock-out transmembrane prostate androgen-induced protein gene suppressed triple-negative breast cancer cell proliferation (Faculty of Medicine Universitas Indonesia, 2017)
Background: Triple negative breast cancer (TNBC) tends to grow more rapidly and has poorer prognosis compared to others. High expression of transmembrane prostate androgen-induced protein (TMEPAI) correlates with poor prognosis in TNBC patients. However, the mechanistic role of TMEPAI in tumorigenic remains unknown. This study aimed to knock-out TMEPAI in TNBC cell line to determine its function further in cells proliferation. Methods: CRISPR-Cas9 has been used previously to knock-out TMEPAI in Hs857T TNBC cell line. Hs587T TNBC parental cell line (wild-type/WT) and TMEPAI knock out Hs 586T cell lines were cultured in Dulbecco's modified eagle medium (DMEM) supplemented with 10% fetal bovine serum, 1% penicillin-streptomycin and amphotericin B. Both cell lines were seeded in 24-well plates and counted every two days, then proliferation rates were plotted. Afterwards, total RNA were isolated from the cells and Ki-67, and TGF-β mRNA expression levels as proliferation markers were determined. Results: Cell proliferation rates as displayed in growth curve plots showed that WT-TMEPAI cell line grew more rapidly than KO-TMEPAI. In accordance, mRNA expression levels of Ki-67 and TGF-β were significantly decreased KO-TMEPAI as compare to TMEPAI-WT. Conclusion: Knock-out of TMEPAI attenuates cell proliferation in TNBC.